Online clustering, fear and uncertainty in Egypt's transition. Issue 6 (19th September 2017) - Lynch, Marc; Freelon, Deen; Aday, Sean
ABSTRACT: Does the uncertainty associated with post-authoritarian transitions cause political and social polarization? Does ubiquitous social media exacerbate these problems and thus make successful democratic transitions less likely? This article examines these questions in the case of Egypt between the 11 February 2011 fall of President Hosni Mubarak and the 3 July 2013 military coup, which overthrew President Mohamed el-Morsi. The analysis is based on a Twitter dataset including 62 million tweets by 7 million unique users. Using a mix of quantitative and qualitative methods, we demonstrate how clusters of users form and evolve over time, the density of interactions between them, and the flow of particular types of information through the clustered network structure. We show that the Egyptian Twitter public developed into increasingly isolated clusters of the like-minded which shared information unevenly. We argue that the growing distance between these clusters encouraged political conflict and facilitated the spread of fear and hatred, which ultimately undermined the democratic transition and won popular support for the military coup.